The P2Y14 receptor in the trigeminal ganglion contributes to the maintenance of inflammatory pain. (December 2019) - Lin, Jiu; Zhang, Yan-yan; Liu, Fei; Fang, Xin-yi; Liu, Meng-ke; Huang, Chao-lan; Wang, Hang; Liao, Da-qing; Zhou, Cheng; Shen, Jie-fei
Abstract: P2Y purinergic receptors expressed in neurons and satellite glial cells (SGCs) of the trigeminal ganglion (TG) contribute to inflammatory and neuropathic pain. P2Y14 receptor expression is reported in the spinal cord, dorsal root ganglion (DRG), and TG. In present study, the role of P2Y14 receptor in the TG in inflammatory orofacial pain of Sprague-Dawley (SD) rats was investigated. Peripheral injection of complete Freund's adjuvant (CFA) induced mechanical hyperalgesia with the rapid upregulation of P2Y14 receptor, glial fibrillary acidic protein (GFAP), interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), C–C chemokine CCL2, phosphorylated extracellular signal-regulated kinase 1/2 (p-ERK1/2), and phosphorylated p38 (p-p38) proteins in the TG. Furthermore, immunofluorescence staining confirmed the CFA-induced upregulation of P2Y14 receptor. Double immunostaining showed that P2Y14 receptor colocalized with glutamine synthetase (GS) and neuronal nuclei (NeuN). Finally, trigeminal injection of a selective antagonist (PPTN) of P2Y14 receptor attenuated CFA-induced mechanical hyperalgesia. PPTN also decreased the upregulation of the GFAP, IL-1β, TNF-α, CCL2, p-ERK1/2, and p-p38 proteins. Our findings showed that P2Y14 receptor in TG may contribute to orofacial inflammatory pain via regulating SGCs activation, releasing cytokines (IL-1β, TNF-α, and CCL2), and phosphorylating ERK1/2 and p38. Highlights: The P2Y14 receptor is functionally expressed in TG and upregulated in CFA-induced oral inflammatory pain. The P2Y14 receptor inhibitor (PPTN) attenuates CFA-induced mechanical hyperalgesia. P2Y14 receptor inhibition decreases CFA-induced SGCs activation, cytokines expression, and phosphorylation of ERK1/2 and p38.